A Descriptive Study On Teaching Reading Descriptive Text To The First Year Student Of SMK Negeri Pringkuku Pacitan In 2012-2013 Academic Year - Erwinandari, Deni, Drs. Djoko Srijono, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This study aimed at describing teaching reading descriptive text to the first year student of SMK Negeri Pringkuku Pacitan in 2012-2013 academic year.This research applies descriptive qualitative research. The researcher collects the data by observing the English class and conducting interview with the teacher and students. The data include syllabus, lesson plan, reading materials, field notes and interview script. And the methods of collecting the data are observation, interview, and documentations. From the research finding and discussion, the researcher draws the following conclusion. First, the process of teaching reading descriptive text to the first year students of SMK Negeri Pringkuku Pacitan in 2012-2013 academic year, they are the methods used by the teacher are Grammar Translation Method (GTM) and Communicative Language Teaching (CLT). Second, the problems faced by the teacher are; (1) the teacher finds difficulties in managing the students in the class, (2) the students have low motivation, (3) each student has different capability in receiving the material, and (4) the teacher has limited time to teach the students. Third, the strategies to overcome the problems are; (1) the teacher can control the class by walking around the class when teaching learning process run, (2) the teacher needs more energy to motivate the students in learning English, (3) the teacher explained the material until the students understand, (4) the teacher needs more time to teach English, (5) the teacher needs more time to communicate with the students, (6) he teacher needs clearing and developing the students' pronunciation, and (7) the teacher needs increasing and memorizing the students' vocabulary. Fourth, the problems faced by the students are; (1) the students have limited of vocabulary, and (2) the students have not clear pronunciation.